The Influences of Transformational Leadership Style and Work Environment on Organizational Citizenship Behavior with Employee Engagement as a Mediating Variable among Non-ASN Employees at the Rectorate of University of Mataram - Slamet Rahadian Cahyadi; Sri Wahyulina; Santy Nururly (Danadyaksa: Post Modern Economy Journal, 2026)
This study aims to analyze the influence of transformational leadership style and work environment on Organizational Citizenship Behavior (OCB), with employee engagement as a mediating variable, among Non-Civil Servant Employees (Non-ASN) at the Rectorate of University of Mataram. A quantitative research approach was employed using a survey method involving 100 respondents, and the data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS). The results indicate that the transformational leadership style did not have a significant direct influence on OCB. Conversely, the work environment had a positive and significant influence on OCB. Furthermore, both transformational leadership style and work environment were found to have a positive and significant influence on employee engagement. In addition, employee engagement had a positive and significant influence on OCB. The findings also reveal that employee engagement significantly mediated the relationship between transformational leadership style and work environment on OCB. These results suggest that employee engagement plays a crucial role in linking leadership practices and workplace conditions with organizational citizenship behavior. Overall, this study highlights that improving OCB among Non-ASN employees at the Rectorate of University of Mataram is not solely determined by leadership style and work environment directly, but also through the strategic role of employee engagement. The findings are expected to provide theoretical contributions and practical implications for human resource management in the higher education sector of University of Mataram.